The Socıo-Economıc Impact of Ngos Development on Benefıcıarıes ın Khyber Pakhtunkhwa Provınce (Kp) of Pakıstan - Anwarul, Mujahid Shah; Wong, Swee Kiong; Syed Arshad, Ali Shah; S. M., Shah (TextRoad Publication, 2018)
This study focuses on the analysis of socio-economic impacts of Non-governmental Organizations (NGOs) development on beneficiaries in Khyber Pakhtunkhwa (KP) of Pakistan. In order to accomplish the task, the qualitative method has been adopted based on the triangulation method in the study. Three fundamental approaches comprising of Regime Theory, Agency Theory, and Theory of Change have been applied to examine the role of NGOs. The findings illustrated a fact that NGO in KP are the root of improving the standard of living of beneficiaries who are poor and socially separated. In opposition, some adverse impacts of these NGOs were found during the 9/11 incident when the beneficiaries were socially divided and poorly developed. However, these impacts do not take over the positivity of NGOs development in KP including the Aga Khan Rural Support Program (AKRSP) and such kinds of other NGOs.